A Light at the End of the Tunnel: How the Right Workplace Structure Can Help Disrupt the Negative Impact of Abusive Supervision. Issue 2 (15th March 2022) - Priesemuth, Manuela; Schminke, Marshall; Bigelow, Bailey; Mitchell, Marie
ABSTRACT: Abusive supervision is costly for organizations because it promotes employee deviance. In this paper, we argue that workplace structure plays a critical role in determining the strength of the relationship between abuse and interpersonal deviance on part of victims. However, theory offers contrasting views of this effect. One view suggests that formalized structures provide clear direction and strict guidance on subordinates' work behaviors, thereby mitigating deviant reactions to abusive supervision. In contrast, a second perspective postulates that formalized structures further burden employees, thereby heightening aggressive reactions to abuse. Results from Study 1 support the mitigating effect of structure. Study 2 replicates and extends these findings by showing that role ambiguity is the underlying psychological mechanism through which formalization lessens employee deviant responses to abuse.